MENEMBUS KOMPLEKSITAS ZAMAN: PERAN SOSIOLOGI DAN ANTROPOLOGI DALAM MEMAHAMI MASYARAKAT MODERN - Alwi Usra Usman; Indriani Indriani; Muhammad Kasim; Rahmat Zulfikar Hamid; Eman Wahyudi Kasim (Universitas Negeri Makassar, 2026)
Modernization is a multidimensional phenomenon that brings rapid and complex social, cultural, and structural changes to modern society. This process not only brings progress in technology and industrialization, but also raises various social challenges such as urbanization, shifting values, changes in family structure, weakening social solidarity, and transformations in religious and cultural relations. Therefore, understanding modern society requires a comprehensive and multidisciplinary scientific approach. This study aims to analyze the role of sociology and anthropology in understanding the dynamics of modern society and their contributions in responding to the challenges of modernity. The research method used is descriptive qualitative with a literature study approach, utilizing secondary data sourced from relevant books and scientific journal articles. The results of the study show that sociology plays an important role in analyzing changes in social structure, social movements, contemporary issues, and the impact of technology and social media on social relations. Meanwhile, anthropology provides a deep understanding of cultural identity, multiculturalism, acculturation, symbols and meanings of popular culture, as well as the application of applied anthropology in modern society. The collaboration between sociology and anthropology allows for a more complete understanding of socio-cultural realities, especially in the context of Muslim communities in Indonesia. Thus, the integration of these two disciplines becomes a strategic analytical framework in formulating inclusive social policies, maintaining cultural diversity, and building social harmony amid the ever-evolving tide of modernization.